2021
DOI: 10.3390/plants10061214
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Cistus sp.: Phytochemical and Antimicrobial Activities

Abstract: Resistance to drugs is reaching alarming levels and is placing human health at risk. With the lack of new antimicrobials drugs, infectious diseases are becoming harder to treat. Hence, there is an increasing awareness of active phytochemicals with therapeutic functions. The tremendous research interest on the Cistus L. genus includes numerous plants used in traditional medicine by people living around the Mediterranean Sea, also resulted in some interesting discoveries and written literature. This review aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 149 publications
(230 reference statements)
0
33
0
2
Order By: Relevance
“…Fungal infections are common in hospitalized patients around the world with several risk factors associated with a shortage of diagnoses [ 41 ]. Many epidemiological data on fungal infections reported that the fungal strains instigated in the present work are involved in a wide range of illnesses.…”
Section: Resultsmentioning
confidence: 99%
“…Fungal infections are common in hospitalized patients around the world with several risk factors associated with a shortage of diagnoses [ 41 ]. Many epidemiological data on fungal infections reported that the fungal strains instigated in the present work are involved in a wide range of illnesses.…”
Section: Resultsmentioning
confidence: 99%
“…Although numerous studies have been conducted to evaluate biological effects of Cistus sp., there is limited research on antibiofilm activity of Cistus sp. against pathogen microorganisms (Zalegh et al, 2021). Hannig et al (2008) revealed that Cistus-tea may be used to reduce the initial bacterial adhesion.…”
Section: Inhibition and Eradication Of Biofilm Formationmentioning
confidence: 99%
“…Turkey has one of the largest floras in Europe and Cistus genus, which is one of the Mediterranean region's characteristic genera, is traditionally used in folk medicine (Catoni et al, 2012;Comandini et al, 2006;Cetin and Yanikoglu, 2006;Attaguile et al, 2000;Ustun and Baykal, 2016). Researchers showed that Cistus species are rich in bioactive compounds such as flavonoids, polyphenols, and terpenoids (Stepien et al, 2018;Barrajón-Catalán et al, 2011;Küpeli and Yesilada, 2007;Zalegh et al, 2021). These compounds are effective in using Cistus species as anti-inflammatory (Demetzos et al, 2001), antibacterial (Benali et al, 2020;Güvenç et al, 2005), antifungal (Barros et al, 2013), antiviral (Ehrhardt et al, 2007), analgesic (Sayah et al, 2017), and antitumoral (Dimas et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Cistus species have been commonly used in folk medicine as herbal tea, extracts, and fragrances in the Mediterranean region, and specifically in Morocco [ 2 ]. Recently, phytochemical profiles and the various pharmacological activities of Cistus species were reviewed, where the antimicrobial activities, including antiviral, antiparasitic, antifungal, and antibacterial potentials, of essential oils, raw extracts, and isolated compounds were introduced [ 3 ]. In the present study, four Cistus species from the High Atlas Mountains of Morocco ( Cistus laurifolius, C. monspeliensis , C. creticus , and C. salviifolius ) which are known to be rich in phenylpropanoids and terpenes were used.…”
Section: Introductionmentioning
confidence: 99%